TAMSIL METAFISIK DAN PENGALAMAN MISTIK DALAM SAJAK-SAJAK CINTA GANDRUNG KARYA A. MUSTOFA BISRI - B.S, Abdul Wachid (Diksi, 2008)
Mustofa Bisri's poetry belongs to the category of poetry that stars frommeaning itself but it is also composed from esthetic mystical experiences, It doesnot rely on the beauty of verbal expression and on language play only. Its estheticquality also lies on the images of esthetic mystical experiences reflected in hispoems. Even if translated into another language, the poems would not lose theesthetic quality.In accordance with the theory of poetry, the language used in the poemspossesses what is often called deceptive simplicity. And in his poems it is assumedto be the result of the basic nature of poetry, that is, indirect expression by way ofdisplacement of meaning, distortion of meaning, and creation of meaning.Keywords: poetry, mystical experience, esthetic quality.